Spatio-temporal dynamics in the mixed fractional nonlinear Schrödinger equation - Aceves, Alejandro; Copeland, Austin (Frontiers in Photonics, 2022)
The effective engineering of linear and nonlinear optical properties in photonic media has led to new advances in the theory and applications of spatio-temporal light–matter interactions. In some instances, research has been motivated by phenomena in a quantum mechanical framework; two notable examples being Anderson localization and parity–time symmetry. Herein, we present theoretical and numerical results on light propagation in the presence of fractional diffraction and classical dispersion, highlighting the role mixed functionality has on stability, spatio-temporal localization, and possible collapse events.